Sleep Issues in Neuromuscular Disorders A Clinical Guide (Springer International Publishing, 2018)
This concise text provides a quick reference to clinically relevant material in both sleep medicine and neuromuscular medicine. Divided into ten chapters, the book begins by laying the foundation for understanding sleep issues in neuromuscular disorders and moves on to offering an overview of sleep disorders in various neuromuscular conditions. Chapters feature practical advice in managing sleep issues, including an overview of noninvasive ventilation. The final part of the book provides useful tables, charts, pictures and flow charts for quick reference in sleep medicine and neuromuscular medicine. Filling a critical gap in the literature, this guide helps anyone treating neuromuscular patients understand the basics of sleep and neuromuscular disorders and its management.